Peningkatan Kemampuan Komunikasi dan Berpikir Kritis Siswa Kelas 3 Tema 6 Subtema 2 Melalui Model PBL di SDI Al Umar Ngargosoka - Agnis Arfiyani; Christiyanti Aprinastuti; MM Suyatini (Pendagogia: Jurnal Pendidikan Dasar, 2021)
This type of research is Classroom Action Research (PTK), the research subject is the 3rd grade students of Al Umar Ngargosoka Islamic Elementary School, totaling 23 students in the 2020/2021 academic year. The object of this research is the students' communication skills and critical thinking on theme 6 sub-theme 2 using the PBL model at Al Umar Ngargosoka Islamic Elementary School. The assessment instruments used were observation sheets, questionnaire sheets, and interview guides for communication and critical thinking. The data analysis technique used in this research is quantitative analysis and descriptive analysis in the form of descriptive words from each table presented. The results of this study indicate: (1) The use of the Problem Based Learning (PBL) model can improve the communication skills of the 3rd grade students, (2) the use of the Problem Based Learning model can improve students' critical thinking from the average score of the initial conditions, (3) an increase Communication skills and students' critical thinking through Problem Based Learning which is carried out by steps a) Orienting the problem, b) organizing students to learn, c) guide the investigation individually or in groups, d) develop and present the work, e) analyzing and evaluating the problem-solving process.